2020
DOI: 10.1039/d0tb00520g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations and understanding of antifouling zwitterionic polymer brushes

Abstract: Zwitterionic materials demonstrate the strong surface hydration to empower their antifouling property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 72 publications
6
75
0
Order By: Relevance
“…Basically, hydration is recognized to be critically important to assess the underwater oleophobicity of SB‐SAMs. Some studies have reported the application of RDF to analyze the distributions between important groups of SAMs 49‐51 . So in this section, the radial distribution functions (RDFs), coordination number ( N ) and residence time ( τ ) of water molecules around SB‐SAMs are analyzed to evaluate their hydration change with different CSLs.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, hydration is recognized to be critically important to assess the underwater oleophobicity of SB‐SAMs. Some studies have reported the application of RDF to analyze the distributions between important groups of SAMs 49‐51 . So in this section, the radial distribution functions (RDFs), coordination number ( N ) and residence time ( τ ) of water molecules around SB‐SAMs are analyzed to evaluate their hydration change with different CSLs.…”
Section: Resultsmentioning
confidence: 99%
“…This latter point seems to constitute the difference between zwitterionic-and ethylene glycol-based coatings [3,7]. Recent computational studies have confirmed the stronger interaction of zwitterionic polymers with water and consequently better antifouling properties [56]. A secondary outcome with a different interfacial water structure between coating classes includes higher resistance of zwitterionic surfaces towards increasing salt concentrations [3,7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they carried out application research on this basis to design and synthesize new antifouling materials. Zheng and coworkers [ 15 , 16 , 17 ] investigated the antifouling properties of zwitterionic polymer brushes, polyacrylamide, and hydroxyalkyl acrylamides using combined molecular dynamics and steered molecular dynamics, believing that the carbon space and anionic groups have distinct effects on their antifouling performance. The state key laboratory of marine corrosion and protection in China has also synthesized a series of antifouling coatings by grafting zwitterionic sulfobetaine methacrylate (T4-SB) or anionic sulfonate methacrylate (T4-SP), which have the property of inhibiting adsorption of proteins on the surface of polysiloxane material (T4).…”
Section: Introductionmentioning
confidence: 99%